Ulam Stability of a Pexiderized Additive-quadratic Equation (European Journal of Pure and Applied Mathematics, 2025)
Suppose that $E$ is a normed space. In this work, using Brzdȩk fixed point theorem, we prove the Hyers-Ulam stability of the Pexiderized additive-quadratic functional equation\begin{align*}f(x+y)+f(x-y)+h(x+y)=2f(x)+2f(y)+h(x)+h(y)\end{align*}for all $x,y\in E$.